2013
DOI: 10.1158/0008-5472.can-13-0728
|View full text |Cite
|
Sign up to set email alerts
|

APOBEC3 Cytidine Deaminases in Double-Strand DNA Break Repair and Cancer Promotion

Abstract: High frequency of cytidine to thymidine conversions were identified in the genome of several types of cancer cells. In breast cancer cells these mutations are clustered in long DNA regions associated with ssDNA, double-strand DNA breaks (DSBs) and genomic rearrangements. The observed mutational pattern resembles the deamination signature of cytidine to uridine carried out by members of the APOBEC3 family of cellular deaminases. Consistently, APOBEC3B (A3B) was recently identified as the mutational source in br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
51
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 50 publications
2
51
0
Order By: Relevance
“…In addition, frequent mutations that can be ascribed to hA3B and hA3A (5=-TC context) were found in host DNA sequences of other cancers, including bladder, cervix, lung, and head-and-neck cancers (25). Kataegis were frequently found near chromosome rearrangement breakpoints (27), and hA3A can induce DNA breaks and activate DNA damage responses (30,74,75). Thus, hA3A may also contribute to cancer development due to its potential genotoxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, frequent mutations that can be ascribed to hA3B and hA3A (5=-TC context) were found in host DNA sequences of other cancers, including bladder, cervix, lung, and head-and-neck cancers (25). Kataegis were frequently found near chromosome rearrangement breakpoints (27), and hA3A can induce DNA breaks and activate DNA damage responses (30,74,75). Thus, hA3A may also contribute to cancer development due to its potential genotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis states that hA3 proteins introduce critical mutations in host genomes that eventually promote cancer progression (19,26,28). Other studies suggested that genomic mutations following double-strand DNA breaks could also be induced by hA3 (29,30). Notably, hA3-associated mutational signatures are highly enriched in HPV-positive cervical and headand-neck cancers (26,31,32).…”
mentioning
confidence: 99%
“…Interestingly, recent work from Halemano and co-workers showed evidence that mouse APOBEC3 mutates immunoglobulin heavy chain variable genes (IgV) during retroviral infections, demonstrating thereby a previously unidentified function of APOBEC3 in generating virus-specific neutralizing antibodies and highlighting a new mechanism for antibody diversification in vivo [50]. In addition, APOBEC3 has also been attributed a role in double-strand break (DSB) DNA repair by non-homologous end joining (NHEJ) [51,52]. Expression of APOBEC3G in lymphoma cells associates with efficient DSB repair, whereas inhibition of APOBEC3G expression or deamination activity results in impaired joining of DSBs by NHEJ, implying a prosurvival role of APOBEC3 in lymphoma cells [51].…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15] Recent evidence suggests that APOBEC3B (A3B) is an important driver of tumor progression in the A3 family. 16,17 …”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15] Recent evidence suggests that APOBEC3B (A3B) is an important driver of tumor progression in the A3 family. 16,17 A3B is a dual domain A3 that prefers to deaminate cytosines at T C motifs in DNA, with weak preference placed on further upstream and downstream bases. 18 Each A3 protein consists of either one or two deaminase domains.…”
Section: Introductionmentioning
confidence: 99%